Pengaruh Mekanisme GCG, Kualitas Audit, dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur di BEI - Partayadnya, I Made Arya; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2018)
This research aims to obtain empirical evidence about the effect of good corporate governance mechanism, audit quality, leverage on the earning management. The population on this research is manufacturing companies listed in Indonesia Stock Exchange at the period 2012- 2016. By purposive sampling technique, got the number samples of 71 companies. Data collection in this research using non-participant observation method that was analyzed using multiple linear regression. Based on the result of analysis concluded that institutional ownership, board of independent commissioner, and leverage have positive effect on the earning management. Audit commite has a negative effect on the earning management. Managerial ownership and audit quality have no effect on the earning management. Keywords: earning management, GCG mechanism, audit quality, leverage